SPEECH INTELLIGIBILITY STUDY - Khayitmuratova Yulduz Iskandarovna (Modern American Journals, 2026)
Speech intelligibility, the measure of how comprehensible spoken language is to a listener, is a critical aspect of effective communication. This study examines the key factors affecting intelligibility, including speaker characteristics, listener perception, environmental conditions, and linguistic complexity. Various methodologies for assessing speech intelligibility, both subjective and objective, are discussed. Applications in education, speech therapy, telecommunications, and artificial intelligence are highlighted. The study also addresses challenges such as individual variability, accent differences, and environmental unpredictability. Understanding and improving speech intelligibility can significantly enhance communication across diverse contexts and technological platforms.
Keywords: Speech intelligibility, communication, speech perception, listener comprehension, acoustic analysis, speech clarity, environmental noise, language learning, speech therapy, artificial intelligence